IMPLIKASI PELAYANAN PRIMA (SERVICE EXCELLENCE) DAN PAKET AGENDA REFORMASI LAYANAN KESEHATAN : PELAJARAN MENARIK DARI SINGAPURA DAN MALAYSIA BAGI INDONESIA - Ignatius Adiwidjaja; Lisa Dhuhaniyati (REFORMASI, 2012)
Excellent service of health sector in Indonesia is very different from the developed countries, especially Singapore and Malaysia. The two countries are more focused on measuring health status over time. Singapore's health in particular is not a static concept and in practice, people in developed countries pay more attention to health changes over time and life expectancy, so the approach to Quality Adjusted Life Year (QALY) to be the focus of the quality of health outcomes. This study aims to describe the factors that encourage patients Indonesia went to Singapore, Singapore's health-care reform at home and take a lesson from hospitals that provide excellent service to the two countries to Indonesia.